The Photoperiod-Insensitive Allele Ppd-D1a Promotes Earlier Flowering in Rht12 Dwarf Plants of Bread Wheat - Chen, Liang; Du, Yingying; Lu, Qiumei; Chen, Hua; Meng, Ruishuang; Cui, Chunge; Lu, Shan; Yang, Yang; Chai, Yongmao; Li, Juan; Liu, Lulu; Qi, Xiangning; et al. (Frontiers in Plant Science, 2018)
The gibberellin-responsive dwarfing gene Rht12 can significantly reduce plant height without changing seedling vigour and substantially increase ear fertility in bread wheat (Triticum aestivum. L). However, Rht12 delays heading date and anthesis date, which hinders its utilization in wheat improvement. To promote early flowering of the Rht12 dwarf plants, the photoperiod-insensitive allele Ppd-D1a was introduced through a cross between Jinmai47 (Ppd-D1a) and Karcagi (Rht12). The results showed that Ppd-D1a can rescue the delaying effect of Rht12 on flowering time and promote earlier flowering by 9.0 days (163.2°Cd) in the Rht12 dwarf plants by shortening the late reproduction phase. Plant height was reduced by Rht12 (43.2%) and Ppd-D1a (10.9%), achieving dwarf plants with higher lodging resistance. Ear fertility, like the grain number per spike, was significantly increased by Rht12 (21.3%), while it was reduced by Ppd-D1a (6.5%). However, thousand kernel weight was significantly reduced by Rht12 (12.9%), while was significantly increased by Ppd-D1a (16.9%). Finally, plant yield was increased by 16.4% and 8.2%, and harvest index was increased by 24.9% and 15.4% in the Rht12 dwarf lines and tall lines with Ppd-D1a, respectively. Clearly, there was additive interaction between Rht12 and Ppd-D1 and the introduction of Ppd-D1a advanced flowering time and improved yield traits of Rht12 dwarf plants, suggesting that the combination of Rht12 and Ppd-D1a would be conducive to the successful utilization of Rht12 in wheat breeding programmes.